1998
DOI: 10.1007/bf02388016
|View full text |Cite
|
Sign up to set email alerts
|

Concentration of radionuclides in building and ceramic materials of Bangladesh and evaluation of radiation hazard

Abstract: The concentration of radioactive 226Ra, 232Th and 4~ in building and ceramic materials of Bangladesh was investigated by y-spectrometry with two HPGe detectors. Radium equivalent activities, representative level index values, criterion formula, emanation coefficients and 222Rn mass exhalation rates were estimated for the radiation hazard of the natural radioactivity in the materials. The activity concentrations of the natural radionuclides, radium equivalent activities, emanation coefficients and 222Rn mass ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
3

Year Published

2009
2009
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(26 citation statements)
references
References 11 publications
0
23
3
Order By: Relevance
“…In addition, the identity and geographic origin of the stones included in this study is not known precisely because naming practices for granite are not standardized (Anjos et al, 2005). Nonetheless, the activity concentrations for 40 K, and the 232 Th and 226 Ra series observed in these stones are within the range reported for granite building materials in the scientific literature (Mustonen, 1984;NCRP, 1987a;Mustapha et al, 1997;Chowdhury, Alam and Ahmed, 1998;European Commission, 1999;Lee, Kim, Lee and Kang, 2001;IAEA, 2003;Kumar, Sengupta and Prasada, 2003;Arafa, 2004;Ahmed, 2005;ICRP, 2005;Al-Saleh and Al-Berzan, 2007;El-Taher, Uosif and Orabi, 2007;Lu, Wang, Jia and Wang, 2007;Ghosh et al, 2008;Kitto, Haines and Diaz Arauzo, 2008;Mujahid et al, 2008). Therefore, these samples of granite intended for use as interior work surfaces contain amounts of naturally occurring radioactive materials that are similar to levels in other types of granite building materials reported in the literature for which larger numbers of samples have been examined.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…In addition, the identity and geographic origin of the stones included in this study is not known precisely because naming practices for granite are not standardized (Anjos et al, 2005). Nonetheless, the activity concentrations for 40 K, and the 232 Th and 226 Ra series observed in these stones are within the range reported for granite building materials in the scientific literature (Mustonen, 1984;NCRP, 1987a;Mustapha et al, 1997;Chowdhury, Alam and Ahmed, 1998;European Commission, 1999;Lee, Kim, Lee and Kang, 2001;IAEA, 2003;Kumar, Sengupta and Prasada, 2003;Arafa, 2004;Ahmed, 2005;ICRP, 2005;Al-Saleh and Al-Berzan, 2007;El-Taher, Uosif and Orabi, 2007;Lu, Wang, Jia and Wang, 2007;Ghosh et al, 2008;Kitto, Haines and Diaz Arauzo, 2008;Mujahid et al, 2008). Therefore, these samples of granite intended for use as interior work surfaces contain amounts of naturally occurring radioactive materials that are similar to levels in other types of granite building materials reported in the literature for which larger numbers of samples have been examined.…”
Section: Discussionmentioning
confidence: 92%
“…A number of studies have reported on the concentrations of natural radionuclides (i.e., activity concentrations) for granite samples obtained from Egypt, Saudi Arabia, Pakistan, South Korea, China, Brazil, Kenya, and Finland (Mustonen, 1984;NCRP, 1987a;Mustapha et al, 1997;Chowdhury et al, 1998;European Commission, 1999;Lee et al, 2001;IAEA, 2003;Kumar et al, 2003;Arafa, 2004;Ahmed, 2005;ICRP, 2005;Al-Saleh and Al-Berzan, 2007;El-Taher et al, 2007;Lu et al, 2007;Ghosh et al, 2008;Kitto et al, 2008;Mujahid et al, 2008). Although the activity concentrations for the majority of those samples were below health-based screening levels and exposure guidelines used in the US, Europe, and elsewhere, a portion of the granite samples had a radiation hazard index that exceeded the European Commission (EC) screening value for limited use as superficial building materials (external dose of 0.3 mSv/a) (European Commission, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…The absorbed dose rate, D (nGy/h) in air at 1m above the ground level owing to the concentration of The mass exhalation rate (E Rn ) and emanation rate coefficient of radon (C Rn ) that can diffuse through the raw and building materials is also a very important radiological index used to evaluate the amount of the 222 Rn emanation fraction released from the building raw materials and products containing naturally occurring radionuclides such as 222 Rn in radioactive equilibrium with its parent. The emanation coefficient of radon (C Rn ) was determined [21] according to:…”
Section: Radiological Hazards For Marble and Granite Used At Shak El mentioning
confidence: 99%
“…The mass exhalation rate of radon is the product of the emanation coefficient of radon (E Ra ) and production rate of radon [21]. The mass exhalation rate (E Rn in Bq/kg·s) is determined using the following equation:  Ra accompanied each other and that the individual result for any one of the radionuclide concentration is a good predictor of the concentration of the other.…”
Section: Radiological Hazards For Marble and Granite Used At Shak El mentioning
confidence: 99%
“…To address these problems, it is necessary to know the dose limits of public exposures and to measure the natural environmental radiation level for the estimation of the exposures to natural radiation sources [5]. Many studies have investigated the levels of natural background radiationby in situ measurements or by analysis of radionuclideconcentration in sand samples [6][7][8][9][10][11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%